The Nexus Between Informal Digital Learning of English and L2 Willingness to Communicate Among Indonesian EFL University Students - Arief Eko Priyo Atmojo; Atin Kurniawati; Yunika Triana; Zahrotun Hanifah (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
This study examined the association between informal digital learning of English (IDLE) activities and willingness to communicate in a second language (L2 WTC) in three distinct communicative contexts: in-class, out-of-class, and extramural digital contexts. A quantitative research method with a correlation design was adopted. A total of 318 Indonesian undergraduate EFL students from four different faculties at one state Islamic university in Central Java participated in an online survey upon invitation. Jamovi 2.2.5 was used to perform statistical computations regarding the reliability test of instruments, the generation of descriptive statistics results, Pearson correlation analysis, and linear regression analysis. The results showed that the students were more engaged in receptive IDLE activities (RIA) than in productive IDLE activities (PIA), although the mean values of both RIA and PIA did not exceed 3.00. In contrast, the mean value of L2 WTC exceeded 3.00, suggesting that the students were generally willing to communicate in English. Regarding correlation, both RIA and PIA were positively associated with L2 WTC. RIA significantly predicted students’ L2 WTC, whereas PIA did not. RIA also explained 15% of the total variance in L2 WTC. This implies that, despite their considerable L2 WTC, students should still utilize digital devices to learn English in extramural digital contexts. Leveraging their enjoyment of PIA, particularly interaction-based PIA, is crucial for promoting two-way communication skills, ultimately benefiting L2 WTC.